Analisis Niat Beli di Usaha Mikro, Kecil, dan Menengah (UMKM) Lingkungan Sekolah pada Siswa SMA Negeri 27 Jakarta Pasca Implementasi Program Makan Bergizi Gratis - Shahira Lazuardy Murod; Dicky Iranto; Tuty Sariwulan (Indo Publishing, 2026)
This study aims to analyze the change in purchase intention of students at SMA Negeri 27 Jakarta toward school-based MSME products following the implementation of the MBG Program, to identify the factors influencing this change, and to examine its impact on the sustainability of MSME businesses. The study employs a descriptive qualitative approach with a case study design, involving eight purposively selected informants: five MBG-recipient students, two MSME vendors, and one teacher serving as the school's MBG program coordinator. Data were collected through semi-structured interviews and documentation, and validated through source, method, time, and theory triangulation. The findings show that the MBG Program does not eliminate students' purchase intention toward MSMEs but rather shifts its orientation from need-based to want-based consumption. Product quality and trust emerged as the most dominant factors shaping purchase intention, followed by attitude toward the product, price, and peer influence. This shift in purchase intention has led to a decline in MSME revenue, although the effect is indirect, mediated by changes in students' consumption behavior. The study also identifies a situational factor beyond the Theory of Planned Behavior framework—the timing of MBG meal distribution—which further shapes students' purchasing patterns throughout the school day. These findings contribute to purchase intention literature by demonstrating that public policy can shape consumer behavior not only through individual psychological processes but also through the mechanics of its own implementation.